Genome wide identification of LcC2DPs gene family in Lotus corniculatus provides insights into regulatory network in response to abiotic stresses - Guangfen Yang; Yujie Liu; Zouxian Gong; Siya Chen; Juanying Wang; Li Song; Shihui Liu (Scientific Reports)
Abstract Low temperatures and drought reduce forage yield and quality, with protein kinases crucial for plant stress response. This study examines the LcC2DPs protein kinase family in Lotus corniculatus, identifying 90 members, with some tandemly distributed on chromosomes 2–6, and grouped into 5 subfamilies (I-V). 34 homologous gene pairs were found in Arabidopsis thaliana. LcC2DP genes promoters contain hormone and stress response elements. GO analysis highlights enrichment in hormone response and kinase activity. Transcriptomic analysis links 78 genes to environmental response and stress growth, with 10 validated by qRT-PCR after treatment with 100 μM ABA and IAA, 20% PEG6000, and 4 °C. Protein interaction analysis identifies 5 core proteins (LcC2DP5, 11, 15, 38, and 58) activated by drought and cold stress. Gene analysis revealed that only LcC2DP5 and LcC2DP15 share co-expression transcription factors, with bZIP, bHLH, WRKY, NAC, MYB-related, MYB, C3H, and C2H2 being prominent. These proteins are expressed under drought and cold conditions, highlighting LcC2DP5 and LcC2DP15 activity. NAC and C2H2 are vital for drought response, while bZIP and MYB-related are important for cold response. This suggests that various LcC2DPs in Lotus corniculatus respond to hormones and stress via a TF regulatory network.